Acute Pain Management using a Combination of Deep Breathing Relaxation and Murotal Al-Qur'an in Clients with GERD: Case Study - Salsabilah, Shofiyah; Ningrum, Dhiajeng Widya; Aisyah, Eryin Nur Rizqi; Rohmah, Linda Sofiana; Ibrahim, Mohammad Anwar; Salsabila, Nadia Ayu; Lestari, Trijati Puspita (Universitas Muhammadiyah Lamongan, 2024)
Introduction: GERD is also called a disease that appears in the stomach and causes gastric disorders. The most common symptoms of GERD are a burning sensation in the throat and chest area, a bitter taste on the tongue, and pain in the heart area. The limited implementation of non-pharmacological deep breathing relaxation therapy using Al-Qur'an murotals is the basis for carrying out research. The purpose of this paper is to analyze acute pain management in patients with GERD Methods: A Case study design was used in this study with a sample size of three patients, namely patients with GERD aged 40-65 years at 'Aisyiyah Bojonegoro Hospital with acute pain nursing problems. The action given to overcome this acute pain by using a combination of deep breath relaxation with Qur'anic murotal given for 3 consecutive days and the pain scale is measured by a numerical pain scale. Data analysis used uses the SMART method (specific, measurable, achievable, relevant and time-bound goals) Results: The results of the case study on the first day of the three patients felt pain in the abdomen with moderate pain category. The planned nursing intervention action is pain management with pain levels as an outcome criterion. Implementation was carried out for 3 days, the results showed that the patient's pain level decreased with a moderate level of pain scale. Conclusion: Deep breathing relaxation therapy with murotal Al-Qur'an can reduce pain levels in patients with GERD. This can happen because deep breathing relaxation can reduce muscle tension and listening to Al-Qur'an murotals with clear rhythm and intonation can foster a feeling of calm and coolness in the heart so that it can reduce stress that has arisen from pain in GERD patients.